Raising kids with big, baffling behaviors : brain-body-sensory strategies that really work - Gobbel, Robyn (Jessica Kingsley Publishers, 2023)
Parenting and neuroscience expert Robyn Gobbel is here to reveal how all behavior, no matter how baffling, can be explained and remedied. You just need to look past the behavior and understand what's going on inside. Robyn decodes the latest brain science into easy-to-understand principles and metaphors to help you become an expert in your child's behavior. She reveals simple ways to help you regulate and connect with your child, with brain, body, and sensory-based strategies to overcome day-to-day challenges.